Hukum Perbankan Syariah dan Implementasinya di Indonesia - Mara rinaldi pakpakhan; M. Yarham; Ridwana Siregar (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The rapid development of sharia business is occurring in the banking, insurance, nodal market and other sharia financial services sectors. However, in supporting its work, the role of the Syanah Supervisory Board (DPS) is needed. The Sharia Supervisory Board (DPS) is an important part of the Sharia Financial Institutions (LKS) in Indonesia. Its position and function are simply regulated in one of the charts in the decree issued by the Indonesian Ulema Council (MUI) regarding the composition of the MUI DSN assignments. Sharia banking law Sharia banking law is a legal framework that regulates banking practices in accordance with Sharia principles, namely Islamic law. These principles include the prohibition of usury (interest), the prohibition of gambling (maisir), the prohibition of investment in businesses considered haram (for example, alcohol and pork), and ensuring fairness and sustainability in financial transactions. In the Sharia banking system, banks follow Islamic economic principles and try to create financial services that are in line with Islamic religious values. This includes the development of financial products such as mudharabah (profit sharing) contracts, musharakah (cooperation) contracts, and murabahah contracts (sale and purchase with disclosed profits). In Sharia banking law, there is a religious authority or board that is responsible for ensuring that all banking transactions and products comply with Sharia principles. Sharia banking law attempts to provide fair and sustainable financial solutions, which are in line with Islamic teachings. For this reason, there are several problems that may hinder the implementation of the Sharia Banking Law and its implementation is not good. Therefore, this research was conducted with the aim of making us know about Sharia Banking Law and its Implementation in Indonesia.